Lineages of “dança afro” in the city of Rio de Janeiro: plural panorama (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
We present a brief mapping of Afrodiasporic dances in the city of Rio de Janeiro – especially what was called “dança afro”. Since the 1950s, a field of action in afro-diasporic dances has been built and demands a critical review of the history of dance, considering afro-referenced bodily perspectives that claim spaces in institutions and denounce the stereotyping of black bodies. Thus, we present the formation of some lineages of “dança afro” in the city, bringing the names of masters and artists in practice and demonstrating the plurality of their artistic proposals as thoughts in dance.
Keywords: afrodiasporic dances; afro-brazilian dance; afro-primitive dance; black dances; plurality in dance